Importance of Close Follow-Up in the Fetus with Premature Atrial Contractions Accompanied by Atrial Septal Aneurysm: A Case Report - Yilmaz Yozgat; Ayhan Kilic; Cem Karadeniz; Rahmi Ozdemir; Onder Doksoz; Timur Mese; Nurettin Unal (Case Reports in Obstetrics and Gynecology)
Rhythms that derive from parts of atria other than the sinus node are called premature atrial contractions (PACs). Vast majority of fetal PACs are idiopathic. Fetal PACs usually have a good prognosis and disappear spontaneously during pregnancy or after delivery. Development of fetal tachycardia or fetal bradycardia is rarely reported during follow-up of fetuses diagnosed with PACs. To the best of our knowledge, coexistence of tachycardia and bradycardia leading to hemodynamic impairment has not yet been reported. We present a fetus diagnosed with PACs and atrial septal aneurysm (ASA) on the 23rd week of gestation proceeding to fetal bradycardia and fetal tachycardia and consequently hemodynamic impairment. We suggest closer follow-up of fetuses with PACs accompanied by ASA.